"Then Potano": Archaeological investigations at the Richardson and White Ranch sites in northern-central Florida. Issue 2 (3rd April 2022) - Boyer, Willet A.; Blanton, Dennis; Ellis, Gary; Marrinan, Rochelle; Mitchem, Jeffrey M.; Smith, Marvin T.; Worth, John E.
ABSTRACT: The town of Potano, refenced in sixteenth-century and in early seventeenth-century Spanish accounts of the exploration and settlement of the Southeast, is one of the named sites associated with the Hernando de Soto entrada that possesses sufficient documentary and archaeological evidence that would allow for its firm identification. The Richardson site, 8AL100, has long been known as a site which has both an early seventeenth-century Spanish and a late precontact/early contact Native American component. We contend, based on the documentary and archaeological evidence, that the Richardson site is the location of the early contact and mission-period town of Potano, and that claims made concerning the White Ranch site, 8MR3538, cannot be substantiated or verified.